2011
DOI: 10.1590/s1678-77572011000100012
|View full text |Cite
|
Sign up to set email alerts
|

Friction between different wire bracket combinations in artificial saliva: an in vitro evaluation

Abstract: ObjectiveThe objective this work was to assess the friction coefficient between brackets and wires of different materials under conditions simulating the oral environment.Material and MethodsStainless steel (SS) and titanium-molybdenum alloy (TMA) wires of 0.019x0.025-in diameter (American Orthodontics) and polycarbonate bracket (American Orthodontics), ceramic bracket (American Orthodontics), and metal bracket (3M Unitek) with slots of 0.022x0.030-in were used. The friction coefficient was assessed by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 25 publications
2
33
0
1
Order By: Relevance
“…Friction is defined as the force opposing the movement of two objects in direct contact to each other and its direction is tangent to a common interface between both surfaces [76]. This concept must be kept in mind in orthodontics since it has an influence on the rate of tooth movement [77].…”
Section: Cold Weldingmentioning
confidence: 99%
See 2 more Smart Citations
“…Friction is defined as the force opposing the movement of two objects in direct contact to each other and its direction is tangent to a common interface between both surfaces [76]. This concept must be kept in mind in orthodontics since it has an influence on the rate of tooth movement [77].…”
Section: Cold Weldingmentioning
confidence: 99%
“…This concept must be kept in mind in orthodontics since it has an influence on the rate of tooth movement [77]. Friction is influenced by many factors, including, but not limited to, the type of bracket and wire materials [76,78]. Researchers have found that the combination between stainless steel wires and brackets display the lowest friction coefficients among regular materials used to manufacture brackets and wires [75,76,78], while the combination between beta-titanium wire and stainless steel bracket showed much higher levels of friction [78].…”
Section: Cold Weldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying friction between wire and bracket in artificial saliva, Fidalgo et al 8) found that the combination between ceramic brackets and stainless steel wire showed a high friction coefficient when compared with the combination of stainless steel wire against polymer (polycarbonate) bracket.…”
Section: Introductionmentioning
confidence: 99%
“…However, the various agents used for maintaining good oral hygiene during orthodontic treatment may affect the physical properties of titanium wires, and thus may increase the frictional forces between ceramic brackets and titanium wires. Consequently, this may affect the outcome of orthodontic treatment [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%